2020
DOI: 10.1021/acsomega.0c03646
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Evaluation of the Radical Scavenging Mechanism of Mactanamide

Abstract: Mactanamide ( MA ) is a diketopiperazine isolated from marine fungi of the genus Aspergillus . This compound is known as a natural antioxidant from experimental studies, yet this activity has not been successfully modeled thus far. In this work, the hydroperoxyl radical scavenging activity of MA was evaluated in the gas phase and physiological environments by thermodynamic and kinetic calculations. The results revealed that the HOO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Thus, in this section, the kinetics of the FX + HOOc reaction was evaluated for this bond by following the (QM-ORSA) protocol and the M06-2X/6-311++G(d,p) method. 9,10,22 The results are presented in Fig. 2 and Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, in this section, the kinetics of the FX + HOOc reaction was evaluated for this bond by following the (QM-ORSA) protocol and the M06-2X/6-311++G(d,p) method. 9,10,22 The results are presented in Fig. 2 and Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…As FX is a phenolic compound, the deprotonation of the OH moieties must be considered in the evaluation of the antioxidant activity in aqueous solution. 9,22 The initial calculation of PA values showed that the site most likely to dissociate is the O7-H bond. Thus, this bond was used to calculate the pK a of FX.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that the deprotonation of the OH bonds plays a key role in the HOO • antiradical activity of phenolic compounds in the aqueous solution [ 30 , 34 , 49 ]. The spontaneous dissociation of acidic moieties practically eliminates the activation energy barrier of the first step of the SPLET mechanism, simplifying it to direct electron transfer, and for this reason, this pathway can become energetically favoured in aqueous solution for the dissociated species.…”
Section: Resultsmentioning
confidence: 99%